Religion and public policy: human rights, conflict, and ethics ; a festschrift in honor of David Little - Little, David; Twiss, Sumner B.; Simion, Marian Gh.; Petersen, Rodney Lawrence (Boston Theological Institute, 2015)
Includes bibliographical references and indexes